A Comprehensive School-Based Nutrition Intervention to Improve the Implementation of Healthy School Canteen Policy: A Systematic Review - Tauhidah, Sarah At; Candi, Cicilya; Bachtiar, Adang (Journal of Health Policy and Management, 2021)
Background: School-based nutrition intervention is recommended as one of the public health strategies in supporting the development of healthy diet behaviour for school-age children. It is in line with Global Action Plan 2013-2020 of World Health Organization (WHO) in preventing and controlling double burden of disease as a consequence of non-communicable disease in the future. This study aims to identify the kind of comprehensive school-based nutrition intervention and analyze effectiveness of every study in improving policy implementation of healthy school canteen.Subjects and Method: This systematic review study was conducted from two electronic databases, namely Scopus and ProQuest with keywords of "school nutritional policy", "comprehensive intervention", and "healthy canteen" to search relevant publication in English and have open access published from 2015 to 2020.Results: From total 1.367 of publications, 9 articles meet inclusion criteria. Based on evaluation of those studies with comprehensive or multi-component intervention to healthy school canteen policy, the common elements show that regular monitoring and feedback with executive and community support can show improvement of school adherence to policy implementation.Conclusion: This study found that a comprehensive school-based nutrition intervention was effective in improving the implementation of healthy school canteen policy.Keywords: nutrition intervention, healthy canteen, policy implementationCorrespondence: Sarah At Tauhidah. Health Policy and Administration Department, Faculty of Public Health, Universitas Indonesia. F Building 1st Floor, Kampus Baru UI Depok 16424, Indonesia. Email: Sarah.at@ui.ac.id.Journal of Health Policy and Management (2021), 06(01): 57-66https://doi.org/10.26911/thejhpm.2021.06.01.06